The influence of the interventionalist's sex on the outcome and complications of transbronchial lung cryobiopsy - Trudzinski, Franziska; Athanasiou, Christos; Eberhardt, Ralf; Michels-Zetsche, Julia D.; Schellenberg, Mavi; Eichinger, Monika; Polke, Markus; Kahnert, Kathrin; Herth, Felix; Kreuter, Michael; Kontogianni, Konstantina (Respiratory medicine, 2024)
Background - To date there are no data on sex aspects evaluating outcomes of interventional pneumology (IP). Our aim was to investigate sex differences in transbronchial lung cryobiopsy (TBLC) outcomes in the diagnosis of interstitial lung disease (ILD). - Methods - All consecutive (TBLC)s performed for ILD evaluation between Nov 17 and Dec 21 at a tertiary referral center for ILDs and IP were analyzed. The indication for the procedure was determined by a multidisciplinary discussion (MDD). Final results including bronchoalveolar lavage (BAL) and histology were discussed in a 2nd MDD and outcomes and procedure related complications were assessed. - Results - TBLC was performed in 406 patients (38.4 % female/67.8 years/FVC 76.8 %). Among 32 interventionalists, 16 females performed 53 % of interventions. Females had longer procedure times (29.9 vs. 26.6 min, p = 0.046), used fluoroscopy more often (76.7 vs. 50.3 %, p < 0.001) and obtained more samples (3.6 vs. 3.2, p = 0.021) than their male counterparts. No difference was found for major bleeding or pneumothorax. MDD was able to conclude on a diagnosis in 88.4 % of interventions performed by women and in 78.5 % performed by men (p = 0.010). In a multivariate analysis, female gender (OR 1.93) and lower FVC% values (OR 0.98) were significantly associated with diagnostic yield, whereas the number of biopsies, professional experience, use of fluoroscopy or antiplatelet drugs were not relevant. - Conclusion - The results of this study strengthen the role of women in endoscopy and may help to motivate women to pursue a career in IP.
Online verfügbar: 13. August 2024, Artikelversion: 16. August 2024
Gesehen am 14.10.2024